Protein kinase CK2 in TGFβ-induced lens epithelial-mesenchymal transition. Issue 1 (1st January 2021) - Oscar, Alexander; Haykin, Vasil; Dimitrova, Violeta; Petkova, Iva; Zdravkov, Yani; Kostova, Stanislava; Veleva, Nevyana; Mitev, Vanyo; Elenkov, Chavdar; Isaeva, Antonia
Abstract: Cataract is a leading cause of reversible blindness. Secondary cataract is the result of migration, proliferation, and epithelial-mesenchymal transformation (EMT) of lens epithelial cells (LECs), induced by transforming growth factor β (TGFβ). The extracellular signal-regulated kinases 1 and 2 (ERK 1/2) and casein kinase 2 (CK2) are important for fundamental cellular processes. This study aimed to evaluate the role of CK2 in the EMT of LECs. Primary LECs cultures were obtained from age-related and type 2 diabetes-induced cataracts. Diabetic LECs were capable of spontaneous in vitro differentiation. Treatment of LECs with TGFβ2-stimulated ERK1/2 activity, which correlated with the expressed α-smooth muscle actin (α-SMA). siRNA-mediated attenuation of the endogenous catalytic subunit (α) of CK2-inhibited ERK1/2 activity and decreased α-SMA expression. This study shows evidence that the function of ERK1/2 is regulated by the constitutively active heterotetrameric protein kinase CK2 in this cellular phenotype. This study enriches the knowledge on LECs physiology in normal and in pathological conditions.